Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Kemampuan Berpikir Aras Tinggi Pada Teks Berita Kelas VIII - Perlita Herlina Siagian (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This research is research and development or Research and Development (R&D) which aims to develop teaching materials for news texts through worksheets based on high-level thinking skills for grade VIII junior high school. The development model used is the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. This research limits development to the development stage. From the stages that have been carried out, the results obtained are that Class VIII students at GKPI Padang Bulan Private Middle School are very interested and need LKPD products in learning. This was obtained through questionnaire data analyzing students' needs for LKPD needs based on high-level thinking skills with a 100% presentation. Through the needs analysis data, the development of LKPD was designed and validated by material experts, design experts, and teacher responses. The results of the study show that "Development of LKPD based on high-level thinking skills in news texts for class VIII" is included in the "very feasible" category. This can be seen from the results of the validation of material experts 80.7% in the "adequate" category, validation of design experts 80% in the "appropriate" category, the teacher's assessment of the field of study is 92.5% in the "very feasible" category, with a final percentage of 84.4% in the "very feasible" category. Therefore, this product is suitable for use in the educational process.